THE USE OF BIO-POEM STRATEGY IN TEACHING WRITING DESCRIPTIVE TEXT ON TENTH GRADE STUDENTS - Rohmatin, Rohmatin; Rufinus, Albert; Rezeki, Yanti Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was the use of bio-poem strategy in teaching writing descriptive text on the tenth grade students of SMAN 1 Rasau Jaya in Academic Year 2017/2018. The objective of this research was to find out the effectiveness of Bio-poem Strategy in teaching writing descriptive text. The method of this research was pre-experimental research one group pretest-posttest design. The instruments of this research were pre-test and post-test. The pre-test was given to know the ability of the students at the beginning before the treatment, whereas the post-test was given to know the ability of the students after the treatment. The sample of this research were 29 students of X IPA2 of SMAN 1 Rasau Jaya in academic year 2017/2018. The result of this research showed that the mean score of pre-test was 63,33 while the post-test was 87,03. The t-test score (14,54)Â was higher than t-tableÂ (2,048) at degree of freedom (df) = N1 (29-1=28) and the result of the effect size was 2,7 where the category was strong effect. The null hypothesis (Ho) was rejected because t-value > t-table (14,54> 2,040) on the level of significance 0,05 and the alternative hypothesis (Ha) was accepted. It also means that the use of bio-poem strategy in teaching writing descriptive text on the tenth grade students of SMAN 1 Rasau Jaya in Academic Year 2017/2018 was effective to improve studentsâ€™ achievement in writing.Keywords: bio-poem strategy, writing, descriptive text, SMAN 1 Rasau Jaya